1992
DOI: 10.1144/gsl.sp.1992.068.01.16
|View full text |Cite
|
Sign up to set email alerts
|

New geophysical evidence for extensional tectonics on the divergent margin offshore Namibia

Abstract: Over 14 000 km of high-resolution multifold seismic data together with gravity and magnetic data provide the opportunity to examine the mechanism and history of rifting on the Namibian continental margin. The region is a completely developed divergent margin containing a pre-rift megasequence of interior cratonic sag origin; two rift basin megasequences dominated by siliclastic deposition; a transitional megasequence and thermal sag megasequences dominated by overlapping progradational wedges. In the Orange Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…This assumption is contradicted by more recent published data showing a significant amount of Tertiary sediments preserved along the Namibian margin (Maslanyj et al, 1992;Light et al, 1992aLight et al, , b, 1993Stewart et al, 2000; Aizawa et al, 2000). Over 1 TWT second of Neogene sediments are actually locally preserved in the Walvis basin.…”
Section: Geometry Of Models 1 Andmentioning
confidence: 90%
“…This assumption is contradicted by more recent published data showing a significant amount of Tertiary sediments preserved along the Namibian margin (Maslanyj et al, 1992;Light et al, 1992aLight et al, , b, 1993Stewart et al, 2000; Aizawa et al, 2000). Over 1 TWT second of Neogene sediments are actually locally preserved in the Walvis basin.…”
Section: Geometry Of Models 1 Andmentioning
confidence: 90%
“…In general, Cenozoic depocenters have an elongated shape parallel to the steep slope and form a thin (50-250 m thick) cover on the continental shelf (Dingle et al, 1983;Light et al, 1992;McMillan, 2003). The Cenozoic-Cretaceous transition is marked by an easily recognizable late Maastrichtian-early Paleocene seismic reflector named reflector D (=Davie) by Emery et al (1975), horizon L by Gerrard and Smith (1982), and reflector SCB-D (Weigelt and Uenzelmann-Neben, 2004;Fig.…”
Section: Cenozoicmentioning
confidence: 99%
“…Based on previous studies (Rabinowitz and LaBrecque, 1979;Light et al, 1992;Clemson et al, 1997) Meisling et al (2001) suggested that seafloor spreading started in the Cape Basin in the middle Hauterivian (anomaly M9; w130 Ma), in the Walvis Basin (conjugate to the Pelotas Basin) in the early Aptian (w120 Ma) and in the Namibia Basin (conjugate to the southern Santos Basin) in the late Aptian (w113 Ma). Salt deposition was widespread in the Santos and Campos basins and was apparently restricted to a short time span in the late Aptian (Davison, 2007;Karner and Gambôa, 2007;Mohriak et al, 2008;Torsvik et al, 2009).…”
Section: Geodynamic Evolutionmentioning
confidence: 99%